Community participation and civic engagement in the digital era : localizing sustainable development - Singh, Mudit Kumar (Emerald Publishing Limited, 2022)
Understanding the challenges in research and practice of participation in the digital era, and the important role of local governance in achieving the sustainable development goals, Community Participation and Civic Engagement in the Digital Era unfolds the complex relationship of community participation, social capital and social networks. Singh presents an in-depth literature review alongside case studies from developing countries, showcasing the role of participation in sustainable development, and explaining how digital development creates technological tools and a virtual space for community engagement - increasing the complexity of community participation and civic engagement, and the potential for implementing the sustainable development goals at a local level. From the historic concept and forms of participation to describing and analysing the environmental and individual factors shaping practice of participation, community development interventions and local governance, the book culminates in a discussion of future work and challenges in the digital world. Delivering a careful review of the theoretical and practical problems of community participation in the digital age and featuring applied theories and cases which appeal to public policy makers and researchers, Community Participation and Civic Engagement in the Digital Era offers a rich theoretical perspective and detailed critical review of social capital and social networks that has profound application in the fields of political science, sociology and development economics.
Keywords: Political participation.; Social action.; Sustainable development.; Political Science -- Political Process -- General.; Political structure & processes.; elektronické knihy; electronic books